2011
DOI: 10.1002/elps.201100216
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of single‐stranded DNA through the α‐hemolysin protein nanopore in acidic solutions

Abstract: The effect of acidic pH on the translocation of single-stranded DNA through the α-hemolysin pore is investigated. Two significantly different types of events, i.e., deep blockades and shallow blockades, are observed at low pH. The residence times of the shallow blockades are not significantly different from those of the DNA translocation events obtained at or near physiological pH, while the deep blockades have much larger residence times and blockage amplitudes. With a decrease in the pH of the electrolyte so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 64 publications
(87 reference statements)
0
41
1
Order By: Relevance
“…30, 31 Values of t̄ t decrease exponentially with increasing voltage (Figure 2A), consistent with RNA translocation. 14, 26, 3234 …”
Section: Resultsmentioning
confidence: 99%
“…30, 31 Values of t̄ t decrease exponentially with increasing voltage (Figure 2A), consistent with RNA translocation. 14, 26, 3234 …”
Section: Resultsmentioning
confidence: 99%
“…For example, Bayley and coworkers reported that when the pH of the electrolyte decreased from 11.0 to 7.5 and then to 5.0, the charge selectivity of the wild-type αHL pore changed from cation selective to weakly anion selective, and then to anion selective (Gu et al, 2001). Our previous studies demonstrated that a reduction in the pH of the electrolyte solution could result in an increase in the event frequency and residence time of biomolecules and terrorist agents in the nanopore, and/or improve the event signature contrast between the target analyte and other matrix components, thus offering an enhanced resolution and better sensitivity for the nanopore sensor (de Zoysa et al, 2011; Gupta et al, 2013). The improved nanopore resolution and sensitivity might be attributed to several factors, such as the enhanced electro-osmotic flow, the pH effect on the charge state of the target analyte, and the analyte/protein ion channel structure or conformational change.…”
Section: Resultsmentioning
confidence: 99%
“…One challenge to develop nanopore sensors is to slow down the translocation of target analytes in the nanopore so that analyte events could be captured by the current recording technique (usually, ∼100 μs event residence time is required). In addition to taking advantage of the experimental conditions to regulate molecular and ionic transport , two major approaches have been utilized in the nanopore sensor design: one involves the structural modification of the nanopore interior to construct binding sites , while the other relies on a host or probe molecule to form host‐guest or probe‐analyte complexes . Although a wide variety of substances have been detected, nanopore detection of many small molecules, especially anions, by these two approaches is not successful.…”
Section: Methodsmentioning
confidence: 99%